The structure of crystallisable copolymers of l-lactide, ε-caprolactone and glycolide - Channuan W. (2014)
We apply a new X-ray scattering approach to the study of melt-spun filaments of tri-block and random terpolymers prepared from lactide, caprolactone and glycolide. Both terpolymers contain random sequences, in both cases the overall fraction of lactide units is ∼0.7 and 13C and 1H NMR shows the lactide sequence length to be ∼9-10. A novel representation of the X-ray fibre pattern as series of spherical harmonic functions considerably facilitates the comparison of the scattering from the minority crystalline phase with hot drawn fibres prepared from the poly(l-lactide) homopolymer. Although the fibres exhibit rather disordered structures we show that the crystal structure is equivalent to that displayed by poly(l-lactide) for both the block and random terpolymers. There are variations in the development of a two-phase structure which reflect the differences in the chain architectures. There is evidence that the random terpolymer includes non-lactide units in to the crystal interfaces to achieve a well defined two-phase structure. © 2005 Published by Elsevier Ltd.